School Effects and Labor Market Outcomes for Young Adults in the 1980s and 1990s - Spyros Konstantopoulos; Amelie F. Constant (Institute for the Study of Labor (IZA), 2003)
This study examines high school effects on the labor market success of young adults, above and beyond individual and family characteristics. We employ data from two longitudinal, nationally probability samples: the National Longitudinal Study and the High School and Beyond study and the 5th and 4th follow-up studies respectively. We employ multi-level models and adjust for selection into the labor force. Our findings reveal that there are differential, enduring school effects on future earnings for individuals attending different schools.
Keywords: C3; C1; A2; J3; J1; 330; school effects; multi-level models; labor market performance; school heterogeneity; Allgemeinbildende Schule; Bildungsertrag; Erwerbsverlauf; Schätzung; Vereinigte Staaten